The Impact of Practical Skills on Improving the Servicemen’s Preparedness to Act in Case of Radiation Contamination of the Area - Dziuba, Petro; Burbela, Serhii; Zhuravel, Vitalii; Marchenko, Bohdan; Verheles, Kostiantyn (International Journal of Statistics in Medical Research, 2024)
The servicemen’s practical skills to respond to threats of chemical, biological, radiological and nuclear attacks, as well as the ability to make effective decisions are necessary for the implementation of effective targeted actions in the face of military threats. The aim of the article is to identify the impact of servicemen’s decision-making skills on their preparedness to act in case of radiation contamination of the area as well as an analysis of the opportunities of skills development in the educational simulation environment. The research employed such empirical methods as: educational experiment, testing, survey, quantitative assessment, and qualitative analysis. The study of causal relationships between servicemen’s decision-making skills under Contaminated Remains Mitigation System CRMS conditions and their preparedness to act under conditions of radiation contamination made it possible to identify a set of decision-making skills that affect high, medium and low servicemen’s preparedness to act under the chemical, biological, radiological, and nuclear (CBRN) attacks. The authors developed and tested a virtual reality training simulator for training decision-making skills in a simulated environment of potential threats using the Zaporizhzhia Nuclear Power Plant (NPP) situation as an example. The results of the assessment of students’ knowledge after the educational experiment showed that simulation training in virtual reality was more effective than training using educational video content. The students of the experimental group (EG) showed a 13.2 points better result (90.6 points) in decision-making accuracy than the students of the control group (CG) (77.4 points).